نحو تحقيق الأمن الغذائي في الجزائر في ظل تحديات الزراعة وأهداف التنمية لعام 2030 - صابور، سعاد (جامعة الوادي University of Eloued, 2025)
تهدف هذه الورقة البحثية إلى دراسة واقع الصادرات والواردات الزراعية والغذائية في الجزائر خلال الفترة 2020-2022، وتحليل أثرها على أوضاع الأمن الغذائي، بالاعتماد على المنهج الوصفي التحليلي، من خلال التطرق أولا إلى مفهوم الأمن الغذائي ودوافع تحقيقه على مستوى العالم، ثم التطرق إلى تحليل واقع القطاع الزراعي في الجزائر في ظل السياسات الزراعية المنتهجة وأهداف التنمية لعام 2030، ثم إلى تحليل تطور الصادرات والواردات الزراعية والغذائية وكذا إلى الميزان التجاري الزراعي ومعدل الاكتفاء الذاتي في الجزائر. وقد تم التوصل إلى أن الزراعة الجزائرية لا زالت بعيدة بعض الشيء عن تسجيل مستوى مقبول من الاكتفاء الذاتي الغذائي، مما يتطلب الإسراع في تنفيذ الاستراتيجية الوطنية الشاملة ضمن رؤية سنة 2030، بالتركيز على الموارد الزراعية المتاحة وتقليل الواردات الغذائية. This research paper aims to examine the state of agricultural and food exports and imports in Algeria during the period 2020–2022, and to analyze their impact on food security conditions. The study adopts a descriptive and analytical approach, beginning with an exploration of the concept of food security and the global drivers behind its achievement. It then analyzes the current state of the agricultural sector in Algeria in light of the implemented agricultural policies and the objectives of the 2030 Development Agenda. Furthermore, the paper investigates the development of agricultural and food exports and imports, the agricultural trade balance, and the self-sufficiency rate in Algeria It has been concluded that Algerian agriculture is still somewhat far from achieving an acceptable level of food self-sufficiency. This necessitates accelerating the implementation of the comprehensive national strategy under the 2030 Vision, with a focus on leveraging available agricultural resources and reducing dependence on food imports.
Towards Achieving Food Security in Algeria in Light of Agricultural Challenges and the Development Goals for 2030
مقال
Keywords: أمن غذائي; قطاع زراعي; واردات غذائية; صادرات غذائية; اكتفاء ذاتي